Construction and characterization of a recombinant human adenovirus vector expressing bone morphogenetic protein 2 - ZHANG, ZHENG (D.A. Spandidos, 2013)
The aim of this study was to construct and characterize a novel recombinant human adenovirus vector expressing bone morphogenetic protein 2 (BMP2) and green fluorescent protein (GFP). The BMP2 gene in the plasmid pcDNA3-BMP2 was sequenced and the restriction enzyme recognition sites were analyzed. Following mutagenesis using polymerase chain reaction (PCR), the gene sequence after the translation termination codon was removed and new restriction sites were added. The mutated BMP2 gene (BMP2(+) gene) was cloned into an adenovirus shuttle vector to obtain pShuttle cytomegalovirus (CMV)-BMP2(+)-internal ribosome entry site (IRES)-hrGFP-1. The adenovirus plasmid pAd CMV-BMP2(+)-IRES-hrGFP-1 was constructed by homologous recombination and was transfected into HEK293A cells, followed by adenovirus packaging. pAd CMV-BMP2 was used as the control. The two types of adenovirus were transfected into marrow stromal cells (MSCs). The expression of BMP2 and GFP, as well as the alkaline phosphatase (ALP) activity of expressed BMP2 were detected. Following mutagenesis, the BMP2 gene sequence and recombinant adenovirus vector were as predicted. The novel adenovirus vector expressed both BMP2 and GFP, indicating that a novel recombinant human adenovirus vector expressing BMP2 had been successfully constructed.